2009
DOI: 10.1186/1472-6963-9-162
|View full text |Cite
|
Sign up to set email alerts
|

The development, design, testing, refinement, simulation and application of an evaluation framework for communities of practice and social-professional networks

Abstract: Background: Communities of practice and social-professional networks are generally considered to enhance workplace experience and enable organizational success. However, despite the remarkable growth in interest in the role of collaborating structures in a range of industries, there is a paucity of empirical research to support this view. Nor is there a convincing model for their systematic evaluation, despite the significant potential benefits in answering the core question: how well do groups of professional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 48 publications
0
40
0
Order By: Relevance
“…9 Learning collaboratives are communities of practice, where groups of people who share concern or passion about a topic, deepen their knowledge and expertise in the topic by interacting on an ongoing basis. 10,11 As the first conducted within academic settings,…”
Section: Introductionmentioning
confidence: 99%
“…9 Learning collaboratives are communities of practice, where groups of people who share concern or passion about a topic, deepen their knowledge and expertise in the topic by interacting on an ongoing basis. 10,11 As the first conducted within academic settings,…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there have been calls to develop CoPs that bring together clinicians, managers, services users, caregivers, and researchers. In some contexts, CoPs play an important role in improving health care performance, reducing professional isolation, and facilitating new technology implementation (19). Factors that support and hinder the success of CoPs in the health care sector remain to be investigated.…”
Section: "Communities Of Practice" To Promote Recoverymentioning
confidence: 99%
“…Eysenbach, Powell, Englesakis, Rizo, & Stern (2004) systematically reviewed the effects of online peer-to-peer interactions in virtual health communities of practice and electronic support groups, but found no robust evidence. An ongoing Australian study (Braithwaite et al, 2009) did a content analysis (Greenfield, Travaglia, Nugus, & Braithwaite, 2007) of the 624 publications on health systems communities of practice identified in their systematic review, which will contribute to an evaluation methodology with evidence based outcome measures for communities of practice and social networks. A systematic review (Fung-Kee-Fung et al, 2008) of regional collaboratives in surgery identified five enablers for effective learning for best practice (establishment of trust, reliable data, clinical leadership, institutional support, and an infrastructure for quality management).…”
Section: Updated Literature Reviewmentioning
confidence: 99%